Multi-framework implementation of the problem management process - Pereira, Ruben (2021)
Many different information technology frame-works have been proposed to assist organi-zations implementing information technol-ogy. However, these frameworks are complex, difficult to implement, and overlap with one another making their simultaneous implementation even more difficult to ac-complish by organizations. This study proposes to develop an overlap-less maturity model that helps organizations deal with the aforementioned problems. The model was applied and evaluated by experts at five organizations. This approach was recognized as useful, complete, and helpful in a multi-framework implementation by prob-lem management (PM) experts. This research provides contributions for academics since it distinguishes itself from the existing studies in the body of knowledge and is a baseline for further investigation.